Construction Techniques for Altering the Form of Chedi during the Ayutthaya Period after Completion - Lerdwimolsak, Suwit (NAJUA: History of Architecture and Thai Architecture, 2024)
Phra Nakhon Si Ayutthaya City, the capital of the Ayutthaya Kingdom, presently finds numerous chedi and various architectural styles as evidence of its historical significance. Past studies on Ayutthaya-period chedi have focused on dating and stylistic development using art history methodologies. However, research on the construction techniques used to alter the forms of chedi remains limited within the field of architectural history, despite its importance for analyzing their dating and evolution. This article aims to present knowledge on the techniques used to modify the forms of Ayutthaya-period chedi after their construction was completed. It adopts a historical architectural study approach, with a particular focus on construction techniques. The study seeks to identify various forms of chedi modifications based on existing evidence, examining the construction techniques employed for each form and the purposes behind these alterations, as well as their impact on the original structures. Chedi from the Ayutthaya period, located in the Phra Nakhon Si Ayutthaya island area and its surroundings, are used as case studies. The study found that the construction of Ayutthaya-period chedi generally involved an initial process of methodically stacking bricks to form the basic shape, followed by plastering the walls and adding decorative stucco. Therefore, in this article, the term “after construction was completed” refers to evidence of additional construction work undertaken after the initial form was established. Evidence from current chedi structures, combined with historical records from the Ayutthaya period, indicates that modifications to chedi forms after their completion employed the same techniques as those used during their original construction. These techniques included brick or laterite construction using load-bearing wall systems and corbel structures—both widely used throughout the Ayutthaya period. Each chedi utilized construction techniques tailored to its specific modification purposes, such as architectural or artistic alterations, proportion corrections, or the structure’s enlarging. Field surveys identified at least four types of modifications: 1) Repairing and restoring only the collapsed sections; 2) Encasing the original chedi closely with additional brickwork; 3) Building a new chedi with an inner chamber over the existing one; and 4) Altering specific architectural or decorative stucco elements. These modifications reflect the cultural and religious beliefs of the Ayutthaya period. The construction of chedi was deeply tied to the Buddhist concept of merit-making, as emphasized in the Mahaparinibbana Sutta and the Maha Kassapa Thera Apadana, which highlight the significance of building Buddhist monuments. Consequently, the destruction of chedi would contradict these intentions. This aligns with the evidence that all post-construction modifications were designed to enhance the integrity, beauty, or scale of the original chedi, demonstrating both the craftsmanship and faith of the period.